Urban Land Consolidation Policy in the Context of Creating a Good Environment According to Spatial Planning in Indonesia - Gede Suacana, I Wayan; Sudana, I Wayan; Wiratmaja, I Nyoman; Rukmawati, Diah (Riviera Publishing, 2024)
The research aims to understand how urban land consolidation can solve these problems and improve environmental quality and maintenance of natural resources by involving active community participation. The research method is qualitative, with documentation techniques as one of the data collection methods, by viewing and analyzing documents created by the subject himself or other people about the topic. Data analysis, which consists of three main activities, namely data presentation, data reduction, and conclusion drawing/verification, is a series of activities inseparable from one another. This research shows that the primary substance in land consolidation is that community participation is necessary to donate part of their land, which will then be used to construct public and social facilities. Therefore, it is essential to socialize land consolidation with land rights holders or participants so that they understand the process and mechanism for implementing the land consolidation project correctly. With this understanding, urban land consolidation can be a problem solver and solution for creating a suitable living environment according to spatial planning and making land available for public and social purposes.